Reading Man Flap for Sacral Pressure Ulcer Reconstruction (Medico Legal Update, 2021)
Background: The treatment of pressure sores represents a great challenge to health care professionals.Although, pressure ulcers management requires a multidisciplinary approach, the soft tissue defects requiringreconstruction are mainly considered for surgical repair. Local myocutaneous and fasciocutaneous flaps canprovide stable coverage of pressure sores.Aim of Study: To evaluate the versatility and outcomes of “reading man flap” in the reconstruction of sacralpressure sores.Patients and Method: Between April 2015 to January 2017, ten patients with sacral pressure sore weretreated by using Reading man flap. The patient’s ages were ranging between 35-65 years (mean 53), 6 ofthem were males, and 4 were females. All of them were subjected to local wound care and managementwithout considerable benefit. We exclude those patients with poor medical status and patients with severecontracture and spasticity. The diameter of the sacral pressure sores ranging from 4cm to 7cm (mean 5.5cm).Results: The “reading man flap” technique was seen to be a useful, versatile and simple flap for coverageof pressure sores, with no postoperative complications in 8 of our patients during the follow up period. Theother 2 patients, one of them developed partial flap necrosis (treated conservatively), and the other onedeveloped recurrence after 2 months.Conclusion: The “reading man flap” was found to be a versatile and easily performed technique for closureof small to medium sized sacral pressure sores.